Facing the COVID-19 outbreak in children with cancer - Antonio Ruggiero; Alberto Romano; Giorgio Attinà (BioExcel Publishing Ltd, 2020)
Europe is now the epicenter of the COVID-19 outbreak. Many concerns have arisen about the management and treatment of children with cancer while researchers are wondering how to deal with this devastating pandemic. In view of the epidemiological and clinical characteristics of the COVID-19 outbreak, it is fundamental to stress that the behavior and hygiene rules adopted by children with cancer must be respected and implemented in order to continue to safeguard their health for the current pandemic.